Nature Reserve - Vagalyuk, Liudmyla; Lisovyy, M.; Tsurkan, R. (NUBiP of Ukraine, 2024)
The study guide contains theoretical material for mastering the normative course of the discipline "Nature Reserve" for students of the specialty 101 "Ecology" of the Bachelor’s degree, which will help future environmental specialists to acquire the necessary minimum knowledge of the ecopolitical, theoretical and practical foundations, regulatory, legal, scientific and institutional support of nature reserve management and the formation of their skills in the protection and management of objects and territories of the nature reserve fund, their creation and expansion. For students, graduate students, teachers and researchers of ecological, biological and agricultural universities specializing in ecology and environmental protection.

В навчальному посібнику викладено теоретичний матеріал для засвоєння нормативного курсу дисципліни «Заповідна справа» для студентів спеціальності 101 “Екологія” освітнього ступеня «Бакалавр», що сприятиме засвоєнню майбутніми фахівцями-екологами необхідного мінімуму знань про екополітичні, теоретичні та практичні основи, нормативно-правове, наукове й інституційне забезпечення заповідної справи та формування в них навиків із охорони і управління об’єктами та територіями природно-заповідного фонду, їх створення та розширення. Для студентів, аспірантів, викладачів та наукових співробітників екологічних, біологічних та аграрних вузів, які спеціалізуються в галузі екології та охорони навколишнього середовища.
Recommended for publication by decision of the academic council National University of Life and Environmental Sciences of Ukraine
Keywords: Ecology; Nature Reserve; природний заповідник; заповідник; Reserve; екологія